Multimorbidity and Genetic Characteristics of DICER1 Syndrome Based on Systematic Review. Issue 5 (July 2017) - Cai, Siyu; Zhao, Wen; Nie, Xiaolu; Abbas, Ali; Fu, Libing; Bihi, Safaa; Feng, Guoshuang; Liu, Tianyi; Lv, Yaqi; Ma, Xiaoli; Peng, Xiaoxia
Abstract : It has been reported that germline DICER1 mutations correlate with a distinctive human disease syndrome. Many published studies within this field have been conducted based on rare cases. We systematically searched bibliographic databases, including PubMed, Embase, and COSMIC for articles which are related to diseases covered by DICER1 syndrome. The weighted summary of mutation frequencies among patients with pleuropulmonary blastoma (PPB), cystic nephroma (CN), and Sertoli-Leydig cell tumor (SLCT) were calculated. Forty-nine eligible articles were included. In total, 72 cases with multimorbidity of DICER1 syndrome were identified. More females (n=46, 64%) presented with multimorbidity than males (n=18, 25%) and the remaining 8 patients' sex were unknown. Nineteen of 72 patients with multimorbidity suffered from another disease that was not yet included in DICER1 syndrome, which would provide potential phenotypes of DICER1 syndrome. The germline DICER1 mutation frequencies in PPB, CN, and SLCT were 66.9%, 73.2%, and 57.1%, respectively. The somatic DICER1 mutation frequencies of PPB, CN, and SLCT were 92.4%, 87.9%, and 43.3%, respectively. Majority of patients with multimorbidity of DICER1 syndrome were mutation positive individuals so that multimorbidity may suggest the possible germline mutation of these patients and their relatives. Abstract : Supplemental Digital Content is available in the text.